(untitled) (La Rivada, 2025)
This article reviews various issues that intersect with the gender perspective as a theoretical view- in rural areas of Latin America, especially in Argentina, to focus on the inequalities that are faced by rural women. The objective of this work is to distinguish these inequalities based on the concepts of gender, care, sustainability of life, extractivism and the feminization of survival in order to analyze and reflect on life, trajectories and experiences. The aim is not only to focus on their representations but also on their practices within the country.